1976
DOI: 10.1161/01.str.7.5.500
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal tract responses (PTR) during hypoxia and hypotension.

Abstract: Sundt TM Jr: Clip-grafts for aneurysm and small vessel surgery. Part 4:Relative application to various aneurysms and repair of anterior communicating aneurysms using a right-angle clip holder. SUMMARY In rats with unilateral carotid artery ligation pyramidal tract responses were studied during hypoxia and during trimethaphan-induced hypotension. Observations on EEG activity during hypoxia suggest that unilateral carotid artery ligation produces a more severe perfusion defect in lateral portions of the hemisphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…These results indicate that following unilateral carotid artery occlusion, circulatory and/or metabolic compensation is sufficient to maintain baseline values in both hemispheres, as has been as noted by others (Salford & Siesjo, 1974; Sengupta et al 1974; Sutter & Wiederholt, 1976; Hoffman et al 1983; Busto & Ginsberg, 1985; Payen et al 1996). The lack of effect of a systemically applied adenosine A 1 antagonist on baseline cerebrovascular parameters has also been observed by others (Bryan & Marshall, 1999; Meno et al 2001).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These results indicate that following unilateral carotid artery occlusion, circulatory and/or metabolic compensation is sufficient to maintain baseline values in both hemispheres, as has been as noted by others (Salford & Siesjo, 1974; Sengupta et al 1974; Sutter & Wiederholt, 1976; Hoffman et al 1983; Busto & Ginsberg, 1985; Payen et al 1996). The lack of effect of a systemically applied adenosine A 1 antagonist on baseline cerebrovascular parameters has also been observed by others (Bryan & Marshall, 1999; Meno et al 2001).…”
Section: Resultssupporting
confidence: 87%
“…The interactions of tissue hypoxia and of reduced hippocampal blood flow (HBF) in this ischaemic model with respect to the adenosine‐mediated depression of synaptic transmission are not known. Systemic hypoxia in the rat is associated with a reduction in mean arterial blood pressure (MAP; Sutter & Wiederholt, 1976; Gervitz et al 2001; Wuyam et al 2002). This hypotension, in turn, is associated with reductions in CBF.…”
mentioning
confidence: 99%
“…A decrease in the MAP, in turn, can be associated with a reduced CBF. Systemic hypoxia is reportedly associated with a reduced MAP in rats[27, 28], and an impaired CBF is believed to be the principal pathological mechanism of hypoxia–ischemia[29]. An increased MAP can lead to an increased CBF, thus alleviating the degree of neurological dysfunction during acute ischemic stroke[30].…”
Section: Discussionmentioning
confidence: 99%
“…Nicholson et al[1970] found permanent deficits in visual discrimination and spatial alterations in monkeys that suffered permanent brain damage in response to hypoxia. Sutter and Wiederholt [1976] showed that hypoxia induced permanent damage to the pyramidal motor system. There is evidence from human beings that perinatal hypoxia can be a frequent cause of death in twins.…”
Section: Part 2: Wgta Testsmentioning
confidence: 99%